2012
DOI: 10.1007/s00520-011-1373-8
|View full text |Cite
|
Sign up to set email alerts
|

Preferred place of care and place of death of the general public and cancer patients in Japan

Abstract: Dying at a favorite place is one of the important determinants for terminally ill cancer patients. The primary aim was to clarify (1) differences in preferred place of care and place of death among the general public across four areas across Japan and (2) preferred place of care and place of death among community-representative cancer patients. A cross-sectional mail survey was conducted on 8,000 randomly selected general population. We examined preferred place of care and place of death using two vignettes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 29 publications
2
61
1
Order By: Relevance
“…This rate of preference for home death is higher than the reported rate for terminally ill patients with cancer in Japan (40%; Nakamura et al, 2010;Yamagishi et al, 2012), similar to that in Canada (53.6%; Stajduhar et al, 2008), and lower than the rate reported for patients receiving palliative home care support services (80%; Alonso-Babarro et al, 2011).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…This rate of preference for home death is higher than the reported rate for terminally ill patients with cancer in Japan (40%; Nakamura et al, 2010;Yamagishi et al, 2012), similar to that in Canada (53.6%; Stajduhar et al, 2008), and lower than the rate reported for patients receiving palliative home care support services (80%; Alonso-Babarro et al, 2011).…”
Section: Discussionmentioning
confidence: 48%
“…However, current knowledge about the factors correlated with the actual place of death of patients with cancer (AlonsoBabarro et al, 2011;Murray, Fiset, Young, & Kryworuchko, 2009) is more extensive than that about the factors associated with their preferred place of death (Gomes et al, 2012). Only three studies have explored preferred place of death among Asian populations (Choi et al, 2010(Choi et al, , 2005Yamagishi et al, 2012), the social and cultural factors as well as healthcare systems of which differ significantly from those in Western countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria included: (1) inability to complete the questionnaire (dementia, cognitive failure, psychiatric illness, language difficulty, or visual loss), (2) severe emotional distress of the family, as determined by the primary responsible physicians, (3) treatment-associated death or death from comorbidity, (4) death in intensive care units, and (5) no family member unavailable. The second criterion was, as in our previous studies [32][33][34][35], adopted on the assumption that primary responsible physicians could identify families who may suffer a serious psychological impact due to the present study, and no formal criteria or psychiatric screening was applied. Families were surveyed 6 to 12 months after the patients' deaths.…”
Section: Settings and Subjectsmentioning
confidence: 99%
“…There are a few studies on mixed populations comprising patients and healthy subjects too, such as the one by Yamagishi et al ,[8] while others such as Fukui et al [9] have focussed on a healthy population. These studies take care of the possible differences of opinion between the sick and the healthy members of the population.…”
Section: Introductionmentioning
confidence: 99%